2006
DOI: 10.1016/j.atmosenv.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile organic compound emissions from desert vegetation of the southwestern US

Abstract: Thirteen common plant species in the Mojave and Sonoran Desert regions of the western US were tested for emissions of biogenic non-methane volatile organic compounds (BVOCs). Only two of the species examined emitted isoprene at rates of 10 mg C g À1 h À1 or greater. These species accounted for o10% of the estimated vegetative biomass in these arid regions of low biomass density, indicating that these ecosystems are not likely a strong source of isoprene. However, isoprene emissions from these species continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 31 publications
1
72
0
Order By: Relevance
“…Although the adsorption and desorption characteristics of polymers used most frequently in emission studies have not been studied quantitatively for key volatiles emitted from plants, studies on organic vapors of environmental concern have suggested that polymers such as neoprene and low-density polyethylene, used by default in commercial systems, have potentially significant adsorption/desorption problems for VOC studies (Allaire et al, 2003;Avison et al, 2001;Hartman, 1999;Hodgson et al, 1998;Manura, 1999). Apart from adsorption on polymers, in commercial gas-exchange systems, traces of silicone oil are present in O-ring seals, and in CO 2 cartridges, and in the match valve of Li-Cor 6400 system, introducing additional memory effects and contamination problems due to solubilization and evaporation of anthropogenic and biogenic VOCs in oil (Geron et al, 2006a).…”
Section: Materials Used In Gas-exchange Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the adsorption and desorption characteristics of polymers used most frequently in emission studies have not been studied quantitatively for key volatiles emitted from plants, studies on organic vapors of environmental concern have suggested that polymers such as neoprene and low-density polyethylene, used by default in commercial systems, have potentially significant adsorption/desorption problems for VOC studies (Allaire et al, 2003;Avison et al, 2001;Hartman, 1999;Hodgson et al, 1998;Manura, 1999). Apart from adsorption on polymers, in commercial gas-exchange systems, traces of silicone oil are present in O-ring seals, and in CO 2 cartridges, and in the match valve of Li-Cor 6400 system, introducing additional memory effects and contamination problems due to solubilization and evaporation of anthropogenic and biogenic VOCs in oil (Geron et al, 2006a).…”
Section: Materials Used In Gas-exchange Systemsmentioning
confidence: 99%
“…Brilli et al, 2009;Calfapietra et al, 2008;Ekberg et al, 2009;Geron et al, 2001Geron et al, , 2006aLavoir et al, 2009;Okumura et al, 2008;Peñuelas et al, 2009). The smaller well-mixed chambers generally reach steady-state more quickly, within seconds to minutes, than larger chambers.…”
Section: Diffusion Problems Associated With Small Chambersmentioning
confidence: 99%
“…The model underestimation points to the existence of a larger-than-modelled biogenic methanol source in such ecosystems. Geron et al (2006) investigated biogenic VOC emissions from common desert plants in the southwestern US. The study was focused on terpenoid emissions but some cut branches were analysed with a PTR-MS system so that emissions of methanol and other compounds could be investigated.…”
Section: T Stavrakou Et Al: Global Methanol Emission Fluxes Deducedmentioning
confidence: 99%
“…Two species in this study, creosote bush and saltbush, were also measured by Geron et al (2006) at a location approximately 100 km northwest of Las Vegas. Our current study and Geron et al both found no significant isoprene emissions from these two species.…”
Section: Creosote Bush and Saltbushmentioning
confidence: 99%
“…b Acacia stenophylla (shoestring acacia) BVOC emissions were used to represent all species of acacia in metropolitan area. c Emission factors from Geron et al (2006) were used to represent Ambrosia dumosa (white bursage).…”
mentioning
confidence: 99%